The cost of healthcare among Malaysian community-dwelling elderly - Roshanim Koris,; Norashidah Mohamed Nor,; Sharifah Azizah Haron,; Tengku Aizan Hamid,; Syed Mohamed Aljunid,; Amrizal Muhammad Nur,; Normaz Wana Ismail,; Asrul Akmal Shafie,; Suraya Yusuff,; Maimaiti, Namaitijiang (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study is to provide a comprehensive estimate of the direct and indirect costs of healthcare services used in a nationally representative sample of community-dwelling elderly in Malaysia as well as the determinants of such health care costs. The rise of chronic non-communicable diseases (NCDs henceforth) is stemming from changes in lifestyle and diet, as well as ageing. The prevalence of NCDs basically increases with age and cause an increases in demand for healthcare services which are associated with higher healthcare costs among the elderly. A survey using multi-stage random sampling techniques recruited 2274 elderly people (60 years and above) in Johor, Perak, Selangor and Kelantan. Overall, a year on average of about RM426.50 of costs was determined to be borne by the sampled elderly Malaysian’s in community-dwellings. The direct costs for outpatient care were RM141.24 and the costs for inpatient care were RM2,527. Meanwhile, the indirect costs for outpatient and inpatient care were RM31.44 and RM524.07 respectively. By using multi regression modelling, healthcare used in private facilities and chronic diseases such as cancer and kidney problem were the predictors that influenced the cost of healthcare among the elderly in the community-dwellings. The higher direct cost implies the higher of out-of-pocket health expenditure will borne by the elderly. The elderly who are unable to bear the healthcare cost should be financially support by the authoritie to protect them trapped into the catastrophic health expenditure. Therefore, these findings highlighted the importance of further research aimed at decreasing the prevalence and severity of these NCDs among the elderly in the Malaysian community-dwellings.